1989
DOI: 10.1128/iai.57.1.117-120.1989
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of two formulations of oral cholera vaccine comprised of killed whole vibrios and the B subunit of cholera toxin

Abstract: Two formulations of oral cholera vaccine were evaluated for safety and immunogenicity in adult volunteers in Thailand, an area with sporadic cholera outbreaks. One formulation consisted of 2 x 1011 killed vibrios and 5 mg of cholera toxin B subunit, as was previously evaluated in North American volunteers, and the other consisted of 1 x 1011 killed vibrios and 1 mg of B subunit, as was recently evaluated in a field trial in Bangladesh. Three doses of each formulation were given with citrate-bicarbonate buffer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Because cholera is an enteric disease it has long been surmised that V. cholerae-specific sIgA, which is secreted into the gut lumen, provides the protective response and thus should be the goal of immunization (102). Indeed, increased levels of sIgA specific against V. cholerae LPS have been found in convalescent sera and intestinal secretions of patients recovering from cholera (139,160,190). Those individuals living in endemic cholera areas have anamnestic sIgA response to V. cholerae vaccination (223,224).…”
Section: Protective Antibody Isotypes Sigamentioning
confidence: 99%
See 2 more Smart Citations
“…Because cholera is an enteric disease it has long been surmised that V. cholerae-specific sIgA, which is secreted into the gut lumen, provides the protective response and thus should be the goal of immunization (102). Indeed, increased levels of sIgA specific against V. cholerae LPS have been found in convalescent sera and intestinal secretions of patients recovering from cholera (139,160,190). Those individuals living in endemic cholera areas have anamnestic sIgA response to V. cholerae vaccination (223,224).…”
Section: Protective Antibody Isotypes Sigamentioning
confidence: 99%
“…The most extensively studied new generation vaccine is a killed WC cholera vaccine, containing either heat-or formalin-killed bacteria of the classical and El Tor biotypes admixed with CT subunit B (CTB) (46,225). Killed V. cholerae vaccines have been tested in volunteers and in field trials (46,160). Field-testing of WC-CTB vaccines revealed excellent protective efficacy (85%) in the first 12 months which was reduced to ϳ50% over 3 years (46).…”
Section: Oral Killed Wc Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most infectious organisms invade or colonize mucosal tissues; therefore an important strategy for the prevention of many diseases is to establich means for inducing S-IgA immune responses. Studies in humans and animals (21,(23)(24)(25)29) have demonstrated that oral administration of microbial antigen vaccines result in the presence of antigenspecific IgA antibodies in several different glandular secretions via the common mucosal immune system (24).…”
mentioning
confidence: 99%
“…The volunteers were from middle-class and lower-middle-class backgrounds and included university students and graduates of a vocational school. To ensure the informed nature of the consent process, the volunteers had to pass a written examination consisting of approximately 20 true-or-false questions on all aspects of the study (8,14). The 24 volunteers were randomized to receive a preparation coded A, B, C, or D, two of which were vaccine and the other two placebo.…”
mentioning
confidence: 99%